Pengaruh Kepemimpinan Motivasi Kerja dan Kedisiplinan Terhadap Kinerja Karyawan Perumda Bpr Bank Gresik - Nur Anita Indahwati; Maulidiyah Amalina Rizqi (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study is motivated by the importance of the talent that must be owned From the company. The survival of a company depends on quality and talent. Employee performance. The purpose of this study is Leadership, motivation, and discipline regarding employee performance at PERUMDA BPR Bank Gresik? This study uses a quantitative approach. The population of this study was all PERUMDA BPR Bank Gresik employees, 52 respondents. Data collection The method used is a questionnaire (questionnaire). The data was retrieved using some Linear regression analysis, first instrument test and classic acceptance test Achieved. The results of this study show that leadership, motivation, and discipline are one. It has a significant positive effect on employee performance. The results of this survey are as follows: Further investigation is being considered by including variables other than those that already exist. In this study.